Developing and sustaining a successful family business : a solution-focused guide - Cauffman, Louis (Professional coaching series., 2022)
"This practical and important book offers ideas, examples, and suggestions that address the challenges inherent to developing and sustaining a successful family business. It explores the complex dynamics involved in working with loved ones and how to pass a business on to a new generation"--